The 2020 Presidential Election
XVII, 199 p. 5 illus., 2 illus. in color.
Keywords: This book adopts a regional approach to understanding 2020 presidential election outcomes, taking into account the tribalism that has come to define contemporary US politics and building a path to 270 Electoral College votes. The authors employ qualitative and quantitative methods to examine electoral outcomes in the Midwest, Southwest, Southeast, and Northeast, enriching contextual understandings of the national results and illuminating nuances in public opinion, voter behavior, and party politics. From this foundation, the book offers a comprehensive assessment of prominent issues in the 2020 campaign, which fundamentally shaped and reshaped the nature of the election. Scholars examine seven key issues, including multiple crises that unfolded during the campaign, to understand how these issues affected public opinion and the 2020 campaign. Luke Perry is Professor of Political Science at Utica College, USA, and Director of the Utica College Center of Public Affairs and Election Research. He is the author of Mormons in American Politics; From Persecution to Power (2012), Mitt Romney, Mormonism and the 2012 Election (2014), Religious Responses to Marriage Equality (2018), and Donald Trump and the 2018 Midterm Battle for Central New York (2019).